2013
DOI: 10.1002/mc.22057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the PNPLA3 gene and hepatocellular carcinoma in USA: Risk and prognosis prediction

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an emerging epidemic with high prevalence in Western countries. Genome-wide association studies had reported that a variation in the patatin-like phospholipase domain containing 3 (PNPLA3) gene is associated with high susceptibility to NAFLD. However, the relationship between this variation and hepatocellular carcinoma (HCC) has not been well established. We investigated the impact of PNPLA3 genetic variation (rs738409: C>G) on HCC risk and prognosis in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 39 publications
2
37
1
1
Order By: Relevance
“…In addition to NAFLD and AFLD, the results of a recent meta-analysis reported by Trépo et al ( 46 ) indicate that the PNPLA3 rs738409 C>G polymorphism is signifi cantly associated with hepatocellular carcinoma in patients of European descent with cirrhosis. The GG genotype was also found to be associated with a higher risk of hepatocellular carcinoma in a US patient population ( 41 ). Taken together, our fi ndings and those from previously published reports demonstrate that the PNPLA3 rs738409 C>G polymorphism increases the risk of liver disease.…”
Section: Sensitivity Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to NAFLD and AFLD, the results of a recent meta-analysis reported by Trépo et al ( 46 ) indicate that the PNPLA3 rs738409 C>G polymorphism is signifi cantly associated with hepatocellular carcinoma in patients of European descent with cirrhosis. The GG genotype was also found to be associated with a higher risk of hepatocellular carcinoma in a US patient population ( 41 ). Taken together, our fi ndings and those from previously published reports demonstrate that the PNPLA3 rs738409 C>G polymorphism increases the risk of liver disease.…”
Section: Sensitivity Analysissupporting
confidence: 83%
“…Other reports have examined the association between the PNPLA3 rs738409 C>G polymorphism and other forms of liver disease, most notably NAFLD, which leads to United States, Taiwan, China, Japan, or Malaysia (39)(40)(41)(42)(43). Indeed, in a Japanese study, Hotta et al ( 44 ) found that the risk of carrying the G allele was 0.44 in control patients and 0.60 in patients with NAFLD.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…1113 Overall survival (OS) was defined as the time between HCC diagnosis and death (as a result of all causes) or end of follow-up (censored observations). Underlying cirrhosis was determined by pathological findings (diagnostic biopsies) and by computed tomography scans.…”
Section: Methodsmentioning
confidence: 99%
“…A third meta-analysis also indicated that the I148M polymorphism is associated with advanced fibrosis, but, most importantly, with greater risk of NASH-related hepatocellular carcinoma [13]. Notably, in a prospective cohort study, the PNPLA3 GG genotype was significantly associated with underlying cirrhosis in patients with hepatocellular carcinoma and represented an independent risk factor for death [14]. Apart from NAFLD, the same SNP plays a role in other liver diseases, including chronic hepatitis C, in which it is associated with steatosis, cirrhosis, lack of response to antiviral treatment and possibly hepatocellular carcinoma [15].…”
Section: New Article In "Metabolism"mentioning
confidence: 95%